2013
DOI: 10.1200/jco.2013.31.15_suppl.9048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRAF mutation and effectiveness of BRAF inhibitor on the brain metastases in patients with metastatic melanoma.

Abstract: 9048 Background: Brain metastases continue to be the major cause of morbidity and mortality in patients with metastatic melanoma. The impact of BRAF mutations and effectiveness of BRAF inhibitors on the brain metastases in these patients is lacking. Methods: Preclinical studies were conducted to assessthe steady-state brain and plasma distribution of vemurafenib, a BRAF inhibitor in FVB wild-type and Mdr1a/b-/-Bcrp1-/- mice deficient in the drug efflux transporters, p-glycoprotein (P-gp) and breast cancer res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A retrospective study showed that vemurafenib did not reduce the incidence of brain metastases. 41 In the Phase I and II studies of vemurafenib, 38% of patients required dose reduction of the drug because of toxic effects, the most common being rash, fatigue, arthralgia, alopecia, photosensitivity, nausea, and diarrhea. 40 Of note, vemurafenib is associated with unique cutaneous toxicities, specifically photosensitivity or eruptive squamous cell carcinoma.…”
Section: Molecularly Targeted Therapy and Its Contribution To Tumor Imentioning
confidence: 99%
“…A retrospective study showed that vemurafenib did not reduce the incidence of brain metastases. 41 In the Phase I and II studies of vemurafenib, 38% of patients required dose reduction of the drug because of toxic effects, the most common being rash, fatigue, arthralgia, alopecia, photosensitivity, nausea, and diarrhea. 40 Of note, vemurafenib is associated with unique cutaneous toxicities, specifically photosensitivity or eruptive squamous cell carcinoma.…”
Section: Molecularly Targeted Therapy and Its Contribution To Tumor Imentioning
confidence: 99%
“…Vemurafenib was associated with a relative reduction of 63% in risk of death and of 74% in the risk of disease progression ( p < 0.001 for both comparisons) 1526 . These data, along with additional subsequent studies, have pushed BRAF inhibitor therapy to the forefront of locally advanced and metastatic cutaneous melanoma 1527–1531 …”
Section: Sinonasal Neuroectodermal and Neuroendocrine Carcinomasmentioning
confidence: 92%